Hadith #3272 - Mishkat al-Masabih (Mishkat al-Masabih)
Ibn ‘Umar said the greatest oath the Prophet used was, “No, by Him who overturns the hearts.” Bukhari transmitted it.
Grade:

Hadith #3273 - Mishkat al-Masabih (Mishkat al-Masabih)
He reported God’s Messenger as saying, “God forbids you to swear by your fathers. If anyone swears he must swear by God, or keep silent.” (Bukhari and Muslim.)
Grade:

Hadith #3274 - Mishkat al-Masabih (Mishkat al-Masabih)
‘Abd ar-Rahman b. Samura reported God’s Messenger as saying, “Do not swear by idols or by your fathers.” Muslim transmitted it.
Grade:

Hadith #3275 - Mishkat al-Masabih (Mishkat al-Masabih)
Abu Huraira reported the Prophet as saying that if anyone swears an oath in the course of which he says, “By al-Lat and al-‘Uzza”, he should say, “There is no god but God”; and that if anyone says to his friend, “Come and let me play for money with you”, he should pay sadaqa. (Bukhari and Muslim.)
Grade:

Hadith #3276 - Mishkat al-Masabih (Mishkat al-Masabih)
Thabit b. ad-Dahhak reported God’s Messenger as saying, “If anyone swears by a religion other than Islam falsely he is like what he has said.* A son of Adam may not take a vow about something which he does not possess, and if anyone kills himself with something in this world he will be punished with it on the day of resurrection. If anyone curses a believer it is like murdering him, if anyone charges a believer with infidelity it is like murdering him, and if anyone makes a false claim to ga
Grade:

Hadith #3277 - Mishkat al-Masabih (Mishkat al-Masabih)
Abu Musa reported God’s Messenger as saying, “I swear by God that if God will, I shall not swear an oath and then consider something else to be better than it without making atonement for my oath and doing the thing that is better.” (Bukhari and Muslim.)
Grade:

Hadith #3278 - Mishkat al-Masabih (Mishkat al-Masabih)
A version has, “Do the thing that is better and make atonement for your oath.’* Bukhari, al-Aiman wan-nudhur, I and Muslim, Aiman, 19 give the first form in full. I have not found the other version.
Grade:

Hadith #3279 - Mishkat al-Masabih (Mishkat al-Masabih)
Abu Huraira reported God’s Messenger as saying, “If anyone swears an oath and considers something else to be better than it he should make atonement for his oath and do that.” Muslim transmitted it.
Grade:

Hadith #3280 - Mishkat al-Masabih (Mishkat al-Masabih)
He reported God’s Messenger as saying, “I swear by God that it is more sinful in God’s sight for one of you to persist in his oath regarding his family than to give for it the atonement God has imposed.” (Bukhari and Muslim.)
Grade:

Hadith #3281 - Mishkat al-Masabih (Mishkat al-Masabih)
He reported God’s Messenger as saying, “Your oath should be about something regarding which your companion will believe you.” Muslim transmitted it.
Grade:

Hadith #3282 - Mishkat al-Masabih (Mishkat al-Masabih)
He reported God’s Messenger as saying, “An oath is to be interpreted according to the intention of the one who takes it.” Muslim transmitted it.
Grade:

Hadith #3283 - Mishkat al-Masabih (Mishkat al-Masabih)
‘A’isha said that the verse, “God will not take you to account for what is futile in your oaths” (Al-Qu’ran 2:225; 5:89) was sent down about such phrases as “No, by God,” and “Yes, by God.” Bukhari transmitted it. Sharh as-sunna has the wording of al-Masabih, saying that some transmitters traced it back to the Prophet on ‘A’isha’s authority.
Grade:

Hadith #3284 - Mishkat al-Masabih (Mishkat al-Masabih)
Abu Huraira reported God’s Messenger as saying, “Do not swear by your fathers, or by your mothers, or by rivals (Cf. Al-Qur’an 2:22 etc. The reference is to idols or false gods) to God; and swear by God only when you are speaking the truth.” Abu Dawud and Nasa’i transmitted it.
Grade:

Hadith #3285 - Mishkat al-Masabih (Mishkat al-Masabih)
Ibn Umar told that he heard God’s Messenger say, “He who swears by anyone but God is a polytheist.” Tirmidhi transmitted it.
Grade:

Hadith #3286 - Mishkat al-Masabih (Mishkat al-Masabih)
Buraida reported God’s Messenger as saying, “He who swears by faithfulness* is not one of our number.” Abu Dawud transmitted it. * Amana. It is held that the objection is due to the fact that the word is not the name of one of God’s attributes, but merely one of the duties prescribed to mankind. It is an unsuitable word because its use suggests that it is being equated with one of God’s attributes.
Grade:

Hadith #3287 - Mishkat al-Masabih (Mishkat al-Masabih)
He reported God’s Messenger as stating that if anyone says, “I am free from Islam,” that is just as he has said if he is lying, but if he is speaking the truth he will not return safely to Islam. Abu Dawud, Nasa’i and Ibn Majah transmitted it.
Grade:

Hadith #3288 - Mishkat al-Masabih (Mishkat al-Masabih)
Abu Sa’id al-Khudri told that when God’s Messenger swore strongly he said, “No, by Him in whose hand is the soul of Abu Qasim.” Abu Dawud transmitted it.
Grade:

Hadith #3289 - Mishkat al-Masabih (Mishkat al-Masabih)
Abu Huraira said that when God’s Messenger swore an oath it was, “No, and I ask forgiveness of God.” Abu Dawud and Ibn Majah transmitted it.
Grade:

Hadith #3290 - Mishkat al-Masabih (Mishkat al-Masabih)
Ibn ‘Umar reported God’s Messenger as stating that if anyone says when swearing an oath, “If God will”, he is not held accountable if he breaks it. Tirmidhi, Abu Dawud, Nasa’i, Ibn Majah and Darimi transmitted it, but Tirmidhi mentioned a number who traced it no farther back than Ibn ‘Umar.
Grade:

Hadith #3291 - Mishkat al-Masabih (Mishkat al-Masabih)
I said, “Messenger of God, tell me what I should do about a cousin of mine to whom I go and ask for something, but who neither gives me anything nor regards my kinship, then when he needs my help comes to me and asks for something, and I have sworn that I would not give him anything or regard his kinship.” He commanded me to do that which is better and make atonement for my oath. In Ibn Majah’s version he told that he said, “Messenger of God, my cousin comes to me and I swear that I will
Grade:

Hadith #3292 - Mishkat al-Masabih (Mishkat al-Masabih)
Abu Huraira and Ibn ‘Umar reported God’s Messenger as saying, “Do not make vows, for a vow has no effect against fate; it is only from the miserly that it is a means by which something is extracted.” (Bukhari and Muslim.)
Grade:

Hadith #3293 - Mishkat al-Masabih (Mishkat al-Masabih)
‘A’isha reported God’s Messenger as saying, “If anyone vows to obey God let him obey Him, but if anyone vows to disobey Him let him not disobey Him.” Bukhari transmitted it.
Grade:

Hadith #3294 - Mishkat al-Masabih (Mishkat al-Masabih)
‘Imran b. Husain reported God’s Messenger as saying, “A vow to do an act of disobedience must not be fulfilled, or one to do something over which one has no control.” Muslim transmitted it. A version has, “No vow must be taken to disobey God.”
Grade:

Hadith #3295 - Mishkat al-Masabih (Mishkat al-Masabih)
‘Uqba b. ‘Amir reported God’s Messenger as saying, “The atonement for a vow is the same as for an oath.” Muslim transmitted it.
Grade:

Hadith #3296 - Mishkat al-Masabih (Mishkat al-Masabih)
While the Prophet was preaching a man was standing, so he asked about him and was told that he was Abu Isra’il who had taken a vow to stand and not to sit, or go into the shade, or speak, but to fast. Thereupon the Prophet said, “Command him to speak, go into the shade, sit and complete his fast.” Bukhari transmitted it.
Grade:

Hadith #3297 - Mishkat al-Masabih (Mishkat al-Masabih)
Anas said that the Prophet saw an old man being supported between his sons, and on asking what was the matter with him and being told that he had taken a vow to walk,* he said, “God most high has no need that this man should punish himself,” and he ordered him to ride. In a version by Muslim on Abu Huraira’s authority he said, “Ride, old man, for God is not in need of you and your vow.” *Mirqat, iii, 565 explains this as a vow to walk to the Ka’ba. (Bukhari and Muslim).
Grade:

Hadith #3298 - Mishkat al-Masabih (Mishkat al-Masabih)
Ibn ‘Abbas told that Sa’d b. ‘Ubada asked the Prophet for a decision about a vow taken by his mother who had died before fulfilling it, and that he gave decision that he should fulfil it on her behalf. (Bukhari and Muslim.)
Grade:

Hadith #3299 - Mishkat al-Masabih (Mishkat al-Masabih)
Ka’b b. Malik told that he said, “Messenger of God, to make my repentance complete* I should divest myself of my property as sadaqa for God and His Messenger.” God’s Messenger replied, “Retain some of your property, for that will be better for you.” So he said he would retain the portion he had at Khaibar. (Bukhari and Muslim.) This is part of a long tradition. * Mirqat, iii, 566 refers this to his withdrawal from the expedition to Tabuk without a valid reason. Pt. 10
Grade:

Hadith #3300 - Mishkat al-Masabih (Mishkat al-Masabih)
‘A’isha reported God’s Messenger as saying, “No vow must be taken to do an act of disobedience, and the atonement for it is the same as for an oath.” Abu Dawud, Tirmidhi and Nasa’i transmitted it.
Grade:

Hadith #3301 - Mishkat al-Masabih (Mishkat al-Masabih)
Ibn ‘Abbas reported God’s Messenger as saying, “If anyone takes a vow but does not name it, its atonement is the same as that for an oath; if anyone takes a vow to do an act of disobedience, its atonement is the same as that for an oath; if anyone takes a vow he is unable to fulfil, its atonement is the same as that for an oath; but if anyone takes a vow he is able to fulfil, he must do so.” Abu Dawud and Ibn Majah transmitted it, but some traced it no farther back than Ibn ‘Abbas.
Grade:

Hadith #3302 - Mishkat al-Masabih (Mishkat al-Masabih)
Thabit b. ad-Dahhak said that in the time of God’s Messenger a man took a vow to slaughter camels at Buwana and came and told him. God’s Messenger asked whether the place contained any idol worshipped in pre-Islamic times and was told that it did not. He asked whether any pre-Islamic festival was observed there and was told that no such thing was observed. He then said to the man, “Fulfil your vow, for a vow to do an act of disobedience to God must not be fulfilled, neither must one to do
Grade:

Hadith #3303 - Mishkat al-Masabih (Mishkat al-Masabih)
‘Amr b. Shu’aib, on his father’s authority, said that his grandfather told of a woman who said, “Messenger of God, I have taken a vow to play the tambourine over you,” to which he replied, “Fulfil your vow.” Abu Dawud transmitted it. Razin added that she said, “And I have taken a vow to perform a sacrifice in such and such a place,” a place in which people had performed sacrifices in pre-Islamic times. He asked whether that place contained any idol worshipped in pre-Islamic tim
Grade:

Hadith #3304 - Mishkat al-Masabih (Mishkat al-Masabih)
bu Lubaba told that she said to the Prophet, “To make my repentance complete* I should abandon my people’s abode in which I committed sin and divest myself of all my property to be given as sadaqa.” He replied, “A third will be enough for you to give.” Razin transmitted it. * The story is given in Ibn Hisham’s as-Sirat an nabawiya (Cairo, 1355/1936), iii. 247. Quraiza had consulted him as to whether they should surrender unconditionally, and while he replied that they should, he put
Grade:

Hadith #3305 - Mishkat al-Masabih (Mishkat al-Masabih)
Jabir b. ‘Abdallah told that a man got up on the day of the Conquest and said, “Messenger of God, I have vowed to God who is great and glorious that if God conquers Mecca at your hands I shall pray two rak’as in Jerusalem.” He replied, “Pray here.” He repeated his statement to him and he replied, “Pray here.” He again repeated it to him and he replied, “Pursue your own course, then.” Abu Dawud and Darimi transmitted it.
Grade:

Hadith #3306 - Mishkat al-Masabih (Mishkat al-Masabih)
Ibn ‘Abbas told that the sister of ‘Uqba b. ‘Amir took a vow to perform the Pilgrimage on foot, but was unable to do so. God’s Messenger then said, “God is not in need of your sister’s walking, so let her ride and present a sacrificial camel.”* Abu Dawud and Darimi transmitted it. *Arabic budana In a version by Abu Dawud it says the Prophet ordered her to ride and offer animals for sacrifice.* In another version by him the Prophet said, “God gets no good from the affliction your
Grade:

Hadith #3307 - Mishkat al-Masabih (Mishkat al-Masabih)
‘Abdallah b. Malik told that when ‘Uqba b. ‘Amir consulted the Prophet about a sister of his who had vowed to perform the Pilgrimage. If barefoot and bareheaded, he said, “Command her to cover her head and to ride, and to fast three days.” Abu Dawud, Tirmidhi, Nasa’i, Ibn Majah and Darimi transmitted it.
Grade:

Hadith #3308 - Mishkat al-Masabih (Mishkat al-Masabih)
Sa’id b. al-Musayyib told that there were two brothers among the Ansar who shared an inheritance and that when one of them asked the other for the portion due to him he replied, “If you ask me again for the portion due to you, all my property will be devoted to the Ka’ba.”1 ‘Umar, telling him that the Ka’ba did not need his property, ordered I him to make atonement for his oath and speak to his brother, for he had heard God’s Messenger say, “An oath or a vow to disobey the Lord,
Grade:

Hadith #3309 - Mishkat al-Masabih (Mishkat al-Masabih)
‘Imran b. Husain told that he heard God’s Messenger say, “Vows are of two kinds, so if anyone vows to do an act of obedience, that is for God and must be fulfilled; but if anyone vows, to do an act of disobedience, that is for the devil and must not be fulfilled, but he must make atonement for it to the extent he would do in the case of an oath.”
Grade:

Hadith #3310 - Mishkat al-Masabih (Mishkat al-Masabih)
Muhammad b. al-Muntashir told of a man who vowed to sacrifice himself if God rescued him from his enemy. He consulted Ibn ‘Abbas who told him to consult Masruq, and when he consulted him he replied, “Do not sacrifice yourself, for if you are a believer, you will kill a believing soul, and if you are an infidel you will hasten to hell; but buy a ram and sacrifice it for the poor, for Isaac was better than you and he was ransomed with a ram.”* He told Ibn ‘Abbas and he replied, “This is
Grade: